Pengaruh Pijat Endorphin terhadap Intensitas Nyeri Pada Ibu Bersalin Kala I Fase Aktif di Klinik Sari Medika Bekasi - Faulina, Riza; Fitri, Rizki Ainul (Universitas Malahayati, 2025)
ABSTRACT Pain during childbirth, if not treated immediately, will result in feelings of worry, fear and stress, thus requiring care to reduce pain during childbirth. One thing that can be done to reduce pain during labor is endorphin massage. This is because touch therapy stimulates the body to release endorphin compounds which are pain relievers and can create a feeling of comfort. Based on this, researchers are interested in conducting research entitled